New insights into vegetable oil pyrolysis by cold plasma technique - Phimpaka Meeprasertsagool (2018)
© 2017 The Authors. Published by Elsevier Ltd. Green liquid fuels are alternatively produced by pyrolysis of vegetable oil. Still, this process requires high processing temperature and high energy consumption per unit cost. Recently, solution/liquid-phase plasma (cold plasma) is the novel method to provide the direct energy at highly excited energy state. In this study, the investigation of the green fuel synthesis from vegetables oils using cold plasma was examined. The cold plasma reactor was connected to a bipolar pulsed power supply under 200 ml of palm oil, the pulse frequency adjusted from 15-45 kHz and the voltage adjusted in ranges of 1.2-1.5 kV with 40 minutes of discharge times, pulse width 2 μs, electrode distance 0.5 mm. Properties of generated plasma were investigated by optical emission spectroscopy (OES) methods. The liquid products were analysed by GC-MS. In order to identify components of the liquid product, a GC-MS chromatogram was carried out; the main peaks were oleic acid and palmitic acid. Therefore, the other peak showed which products were cracked to short-chain hydrocarbon and hexadecane was one of the compounds which were cracked in palm oil. In conclusion, the results showed that plasma has potential and enough energy to convert vegetable oils in liquid fuels at room temperature which can also provide the direct energy better than pyrolysis.